How accurate are manufacturers' recommendations in determining ineligibility for transfemoral transcatheter aortic valve implantation? - Çakal, Beytullah; Çakal, Sinem; Karaca, Oğuz; Kızılırmak Yılmaz, Filiz; Güneş, Hacı Murat; Yıldırım, Arzu; Güler, Yeliz; Özcan, Özgür Ulaş; Boztosun, Bilal (Sociedade Portuguesa De Cardiologia, 2023)
Introduction: Up to one-third of patients indicated for transcatheter aortic valve implantation (TAVI) may be unsuitable for transfemoral TAVI (TF-TAVI) according to manufacturers' recommendations and numerous professional societies. Objective: This study aimed to investigate the predictive value of manufacturers' guidelines for major vascular access site complications using the Perclose ProGlide device. Methods: Among 208 patients undergoing TF-TAVI, 144 patients (69.2%) were deemed eligible for TF-TAVI according to the manufacturer's instructions. A minimal lumen diameter (MLD) of the femoral artery below the manufacturer's specified limits and/or the presence of circumferential calcification were the reasons for ineligibility. Calcium score (CS), sheath-to-femoral artery ratio (SFAR) and MLD were estimated from computed tomography imaging. Vascular complications (VCs) (defined according to VARC-2 criteria) were retrospectively compared. Results: Patients in the ineligible group had higher SFAR (1.13±0.15 vs. 0.88±0.107, p<0.001) and CS (1.66±0.99 vs. 1.24±0.73; p=0.003), and significantly lower MLD (7.72±1.03 vs. 6.31±0.96 mm; p<0.001) compared to the eligible group. Major (6.3% vs. 12.3%, p=0.13) and minor VCs (10.4% vs. 15.6%, p=0.29) were similar in the eligible and ineligible groups. The ineligible group had higher rates of rupture (0.7% vs. 6.3%; p=0.03). SFAR was the only independent predictor of major VCs (OR 469.1, 95% CI 4.95-44466.57, p=0.008). Conclusion: The TAVI team should not decide whether the patient is suitable for a femoral approach based solely on the manufacturer's criteria, and should incorporate additional factors that could be predictive of major VCs.
Keywords: Acesso Vascular; Aortic Valve Disease; Complications; Complicações; Doença Valvular Aórtica